Implementasi Sinkronisasi File Server Dengan Secure File Transfer Protocol - Feldy Novanda Mulkan; Lalu A. Syamsul Irfan Akbar, ST., M.Eng.; Cipta Ramadhani, ST., M.Eng. (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2024)
The web serves as a platform for disseminating and retrieving information. However, during periods of server overload, server performance and client access times can significantly slow down. One viable solution to address this issue is server clustering, where multiple servers are combined into a unified system. Among the methods employed in such scenarios is load balancing, which aims to evenly distribute client requests across multiple servers to optimize performance. Nevertheless, ensuring file synchronization across these clustered servers remains crucial to maintain file availability. Python's watchdog library provides a solution for monitoring file changes and facilitating file synchronization using Secure File Transfer Protocol (SFTP). In synchronization tests, file transfer speeds ranged from 39.54 to 42 Mb/s, with transfer durations varying between 2.02 seconds and 19.05 seconds for file sizes ranging from 10MB to 100MB. Concurrent synchronization experiments revealed that 9 files failed due to data collisions caused by simultaneous file transfers to both servers. Furthermore, the experiments successfully differentiated and compared the MD5 values of each file, demonstrating the capability to detect changes when files were created, deleted, or modified during alternate synchronization processes.